Pemberdayaan Dan Pelatihan SDM UMKM Melalui Pelatihan Pengelolaan Keuangan Bagi Usaha Mikro Kecil Dan Menengah di Kabupaten Bengkulu Utara - Zulyanto, Aan; Mukadar, Amir; Suhendra, Chairul; Pertiwi, Dinal Eka; Nazar, Nazar (JURNAL ABDIMAS SERAWAI, 2023)
In 2020, the Ge-ARU (North Bengkulu I Love Products Movement) MSME Association was formed, one of the goals of which is to make North Bengkulu Regency an environmentally friendly, technology-based business city. With a current membership of 712 MSMEs engaged in the following fields: culinary, palm oil waste utilization, sales of agricultural products and processing, and others. One form of human resource development effort can be done through training because training can improve skills and knowledge. Currently, the need for training in the community and MSMEs is very important to increase the productivity and quality of good MSMEs. Several MSME groups have the potential to develop skills through training; one of the training activities that will be carried out is the financial management strategy for MSMEs. In this service, the activities carried out are as a solution to existing problems, namely providing education, socialization, and assistance on Financial Management Strategies for MSMEs. Some of the materials provided include financial conditions, asset status, debt, capital, business planning, and several other financial strategies, including the preparation of good financial reports for MSMEs.